ABSORPSI KULTURAL: FETISHISASI KOMODITAS KOPI - Hery Prasetyo (LITERASI: Indonesian Journal of Humanities, 2014)
Coffee in everyday life of the society can not be separated from the contextualizing and and marginality placing it in the market. What makes it attractive to market is part of the formation of cultural values. The consequences of the emergence of cultural values are the presence of the cultural absorption of the locality to be displayed as part of globality. Coffee culture of the indigenous people of Using, is diametrically located in the global cultural space. The Using people who have been formed by agrarian culture running under the modernization looks stumbling when it is displayed as global. It starts with the formation of culture that is slowly changing self-awareness of indigenous peoples and accompanied by accelerated commodification of local culture. Coffee culture that comes from the local, at the same time faced with the presence of commodities and cultural formations to enjoy it. The coffee culture locality of the customary indigenous community formed within the marginality of the cultural taste to display the dominant and market oriented one. While the formation of postcolonial subjects who were trapped in the cracks of origin of awareness and articulation of cultural banality becomes commonly observable as part of the everyday practices of the people of Banyuwangi. Keywords: cultural absorption, fetishism, locality, post-colonial